The Relationship between Social Support and Psychological Capital with Burnout among School Counselors: A Systematic Literature Review - Neni Husniawati; Dede Rahmat Hidayat; Herdi; Susi Fitri (Universitas PGRI Yogyakarta, 2026)
This study aims to identify the role of social support and psychological capital (Psychological Capital/PsyCap) in reducing the rate of burnout in school counselors and educators through the Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. A total of 20 scientific articles published between 2007 and 2025 were analyzed thematically and statistically descriptively. The study's results indicate that social support from colleagues, supervisors, and the organizational environment has a significant negative impact on burnout. In addition, PsyCap, which includes self-efficacy, hope, optimism, and resilience, is a mediating factor that strengthens the relationship between social support and burnout. These findings support and confirm the importance of collaboration between social and psychological factors in maintaining the mental well-being of educators. Practically, educational institutions need to develop social support-based interventions and strengthen psychological capital (PsyCap) as a sustainable strategy for preventing burnout. Keywords: psychological capital, social support, fatigue, counselor welfare, quality education, good health and well-being